Analisis Kendala Perawat Dalam Melaksanakan Komunikasi Terapeutik Di Lingkungan Pelayanan Kesehatan - Pannyiwi, Rahmat; Azis, Moh. Nisyar Sy. Abd.; Rahmat, Rezqiqah Aulia (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Therapeutic communication is a core skill in nursing practice that directly impacts the quality of care and patient safety. However, nurses often experience various obstacles, resulting in suboptimal implementation of therapeutic communication. This study aims to analyze the obstacles faced by nurses in implementing therapeutic communication in healthcare facilities. The research method used a qualitative descriptive approach with in-depth interviews with 15 nurses in hospitals and community health centers. The results showed that the main obstacles included high workload, lack of communication training, language barriers, patient emotional states, and an unsupportive work environment. The analysis revealed that organizational and individual factors play a role in reducing the effectiveness of therapeutic communication. This study emphasizes the importance of regular training, workload management, and creating a conducive communication environment to improve the quality of the nurse-patient relationship.